An extract of Lycium barbarum mimics exercise to improve muscle endurance through increasing type IIa oxidative muscle fibers by activating ERR? - Meng, J.; Lv, Z.; Sun, C.; Qiao, X.; Chen, C. (The FASEB Journal, 2020)
Lycium barbarum berry (gouqi, Goji, goji berry, or wolfberry), a traditional medicine and functional food, has a wide range of biological effects, including immuno-modulation, anti-aging, antitumor, neuro-protection, and hepato-protection. However, thus far, little is known about the traditional effects of L. barbarum on strengthening muscles. Therefore, this study focused on the effects of an extract of L. barbarum on skeletal muscles. First, the extract of L. barbarum significantly increased the mass of the tibial anterior muscle and gastrocnemius muscle and improved the average running distance of mice. Then, in vivo and in vitro experiments showed that the extract enhanced muscle endurance by increasing the proportion of type IIa oxidative muscle fibers and aerobic respiration. In an in-depth study of the molecular mechanism of these effects, we found that the extract upregulated the proportion of type IIa oxidative muscle fibers by activating ERR? and that the PKA-CREB signaling pathway was involved in its activation. This study is the first to show that L. barbarum extract modulates skeletal muscle remodeling and has mimetic effects on skeletal muscles in a manner similar to exercise. It provides a scientific explanation based on modern biological technologies and concepts for the traditional function of L. barbarum in improving muscle fitness. This study lays a theoretical foundation for the application of L. barbarum in skeletal muscles as an exercise mimetic.